2016
DOI: 10.1017/s136898001600166x
|View full text |Cite
|
Sign up to set email alerts
|

Household food security and breast-feeding duration among Canadian Inuit

Abstract: Our research does not support the hypothesis that children living in food-insecure households were breast-fed for a longer duration than children living in food-secure households. However, we found that more than 50 % of mothers in food-insecure households continued breast-feeding well beyond 1 year. Many mothers in food-secure households also continued to breast-feed beyond 1 year. Given the high prevalence of food insecurity in Inuit communities, we need to ensure infants and their caregivers are being adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We found a high rate of ARI admissions among infants from Nunavut, with RSV being the leading pathogen identified, though fortunately with a relatively low rate of in hospital mortality in the ten-year period. The underlying reasons for these high rates of hospitalization are likely multifactorial and may include social determinants of health disparities, such as high levels of food insecurity (12) and crowded housing (13), potential genetic determinants (14), or challenges in geographically remote communities where thresholds for admission/transfer differ from southern centres. On average, 13.4% of Nunavut’s infant population were hospitalized for ARIs each year; of these, seven in ten were hospitalized outside of Nunavut and approximately one in six admitted to intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…We found a high rate of ARI admissions among infants from Nunavut, with RSV being the leading pathogen identified, though fortunately with a relatively low rate of in hospital mortality in the ten-year period. The underlying reasons for these high rates of hospitalization are likely multifactorial and may include social determinants of health disparities, such as high levels of food insecurity (12) and crowded housing (13), potential genetic determinants (14), or challenges in geographically remote communities where thresholds for admission/transfer differ from southern centres. On average, 13.4% of Nunavut’s infant population were hospitalized for ARIs each year; of these, seven in ten were hospitalized outside of Nunavut and approximately one in six admitted to intensive care.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the adjusted analysis they found no significant association [ 19 ]. At the same time, McIsaac et al (2015) found a non-significant negative association between cessation of breastfeeding and food insecurity in the final model (HR 0.84; 95% CI 0.63-1.11) [ 21 ]. For his part, Dinour et al (2020) found that women with food insecurity during a 12-month period had a 35% risk of stopping breastfeeding during the fourth and sixth week compared to women with food security (RR 0.65; 95% CI 0.50-0.85) [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…This substantiates the findings of Gross et al (2019) and Lesorolog et al (2018), which explain that this may be due to the perception of the relationship between an unhealthy diet and the quality of breast milk [ 17 , 23 , 24 ]. In contrast, Wong et al (2019) and McIsaac et al (2015) found that mothers with food insecurity could be less likely to stop breastfeeding [ 19 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations